Reliability Analysis of Systems Subject to Imperfect Fault Coverage Considering Failure Propagation and Component Relevancy - Wu, Chuanli; Wang, Zixiang; Zhou, Siwei; Zhao, Dongdong; Tian, Jing; Xiang, Jianwen (2021 IEEE International Symposium on Software Reliability Engineering Workshops (ISSREW), 2021)
This paper proposes a method to analyze the component relevance and the failure propagation in the system subjected to imperfect fault coverage (IFC). In fault-tolerant systems, uncovered component failures may directly lead to a system failure because the non-isolated component failures may propagate through the system, or the system cannot be reconfigured to eliminate the impact of relevant component failures. The failure effect of components is studied and divided into propagated failures and non-propagated failures according to whether the effects of failure could spread. The fault-tolerance is described by isolation phase and reconfiguration phase in this paper which are supposed to be independent. In our method, the not-isolated propagated component failure can lead to system failure and the not-reconfigured relevant component failure also can lead to system failure. Our experiments show that compared to the traditional imperfect coverage model, the proposed approach can analyze system reliability more accurately based on the same example system.